Research on harmonic optimization and suppression of distributed photovoltaic storage and distribution networks by improving PSO - Pei, Honglan; Yan, Guangying; Zhao, Yingxin; Zhang, Wenqiang; Xiao, Chun (Frontiers in Mechanical Engineering, 2025)
IntroductionWith the continuous increase in the penetration rate of distributed photovoltaic and energy storage systems in distribution networks, the deterioration of harmonic pollution problems poses a threat to the safe operation of the power grid.MethodsThis paper proposes an improved particle Swarm optimization algorithm (IPSO) for optimizing the harmonic suppression strategy of distributed photovoltaic energy storage distribution networks. By introducing weighted average and fuzzy control, the problems of poor search accuracy and local optima in traditional algorithms can be solved. Based on the harmonic distortion rate objective function of the filter device, the optimal configuration of the capacity and position of the filter device is achieved through an improved algorithm, effectively suppressing the harmonics in the distribution network and improving the power quality of the distribution network. To test the feasibility of the strategy, simulation experiments were conducted.ResultsThe results showed that after the harmonic suppression device was installed in the distribution network, the distortion rate of the grid-connected current decreased from 19.99% to 2.54%, verifying the effectiveness of the proposed strategy in reducing current harmonic distortion and improving the quality of the current waveform.DiscussionIt can be seen that it is feasible to optimize and suppress harmonics in distributed photovoltaic storage distribution networks by improving the Particle Swarm Optimization (PSO)algorithm, providing new ideas for harmonic control in distribution networks under the high proportion of renewable energy access and promoting the development of the domestic power industry.